PERFORMANCE EVALUATION OF MODIFIED AODV AGAINST BLACK HOLE ATTACK IN MANET - Kaushik, Neha; Dureja, Ajay (European Scientific Journal, ESJ, 2013)
A mobile ad-hoc network is an infrastructure less network which consists of a number of mobile nodes that dynamically form a temporary network for the transmission of data from source to destination. They are composed of nodes that relay on each other to manage and for secure transmission of traffic due to lack of centralized administration. As MANETs become widely used, the security issue has become one of the primary concerns for all the times. One of the well known attack is the Black Hole attack which is most common in the on-demand routing protocols such as AODV. In this paper, the proposed solution is to modify the AODV routing protocol in such a way that it can combat the cooperative Black Hole attack. The results show an effective increase in throughput and PDR and decrease in average end-to-end delay with a slight increase in routing overhead.